Development of Digital Twins to Optimize Trauma Surgery and Postoperative Management. A Case Study Focusing on Tibial Plateau Fracture - Aubert, Kévin; Germaneau, Arnaud; Rochette, Michel; Ye, Wenfeng; Severyns, Mathieu; Billot, Maxime; Rigoard, Philippe; Vendeuvre, Tanguy (Frontiers in Bioengineering and Biotechnology, 2021)
Background and context: Surgical procedures are evolving toward less invasive and more tailored approaches to consider the specific pathology, morphology and life habits of the patient. However, these new surgical methods require thorough preoperative planning and an advanced understanding of biomechanical behaviors. In this sense, patient-specific modeling is developing in the form of digital twins to help personalized clinical decision-making. Purpose: This study presents a patient-specific Finite Element model approach, focusing on tibial plateau fracture, to enhance biomechanical knowledge to optimize surgical trauma procedures and improve decision-making in postoperative management. Study design: Level 5 Methods: We used a postoperative 3D X-ray image of a patient who suffered from depression and separation of the lateral tibial plateau. The surgeon stabilized the fracture with PolyMethylMethAcrylate cement injection and bi-cortical screw osteosynthesis. A digital twin of the patient’s fracture was created by segmentation. From the digital twin, four stabilization methods were modeled including two screw lengths and whether or not to inject PMMA cement. The four stabilization methods were associated with three bone healing conditions resulting in twelve scenarios. Mechanical strength, stress distribution, interfragmentary strains and fragment kinematics were assessed by applying the maximum load during gait. Repeated fracture risks were evaluated regarding to the volume of bone with stress above the local yield strength and regarding to the interfragmentary strains. Results: Stress distribution analysis highlighted the mechanical contribution of cement injection and the favorable mechanical response of uni-cortical screw compared to bi-cortical screw. Evaluation of repeated fracture risks for this clinical case showed fracture instability for two of the twelve simulated scenarios. Conclusion: This study presents a patient-specific finite element modeling workflow to assess the biomechanical behaviors associated with different stabilization methods of tibial plateau fracture. Strength and interfragmentary strains were evaluated to quantify the mechanical effects of surgical procedures. We evaluate repeated fracture risks, and provide data for post-operative management.